Analisis Peningkatan Pemeriksaan Sifilis pada Ibu Hamil di Puskesmas Tanah Jambo Aye Kabupaten Aceh Utara - Futry Maysura; Nurmakiah Nurmakiah (Pusat Riset dan Inovasi Nasional, 2025)
Syphilis or lion king disease is a sexually transmitted infection (STI) caused by the bacteria Treponema pallidum. Syphilis can be transmitted through sexual intercourse, blood transfusions, and from mother to fetus. Serological tests for antibody detection include non-treponemal tests to screen and evaluate treatment as well as treponemal tests to confirm the diagnosis. Pregnant women are more susceptible to suffering from sexually transmitted infections (STIs) due to changes that occur during pregnancy, including changes in immune, hormonal and anatomical responses, which can change the clinical manifestations of STIs and cause problems in their diagnosis and implementation. Pregnancy affects the mother's defense mechanisms through suppressing the immune system. Genital infections that spread hematogenously and enter the fetal circulation will cause defects, stunted growth, and even cause the fetus to die in the womb. For this reason, pregnant women are advised to undergo screening and treatment as early as possible from the beginning of pregnancy so as to reduce the risk of pregnancy. According to the results of a survey at the Tanah Jambo Aye Community Health Center, North Aceh Regency, information was obtained that the number of pregnant women in 2024 will be 876 pregnant women and 35 boxes of rapid kits containing 25 rapid syphilis tests will be used. This study aims to see the description and level of awareness of pregnant women regarding the results of syphilis examinations at the Tanah Jambo Aye Community Health Center, North Aceh Regency